Role of Stingless Bee, Tetragonula pegdeni and European Honey Bee, Apis mellifera in the Pollination of Confectionery Sunflower - Sawatthum, Anchalee (Thai Journal of Science and Technology, 2020)
The confectionary sunflowers (Helianthus annuus L.) are not self-pollination. It needed pollinators for the seeds producing. This experiment aimed to find the suitable pollinators to increase the seed yield. There were two experiments. The first part tried to find the number of stingless bees (T. pegdeni) and European honey bees (A. mellifera,), visited the two confectionery sunflowers (Chiang Rai and Hungary) cultivars and one hybrid sunflower (Pacific 77). The number of those two pollinators visiting the sunflowers at every 10 minutes of each hour from 06:00 am to 06:00 pm for 5 days were counted. In the second experiment, the efficiency of the pollination by the selected pollinators on the Chiang Rai cultivar was compared. The RCBD was used with four treatments; pollination by stingless bee, pollination by European honey bee, open- pollination, and close-pollination. The LSD method was used for means comparison of the three replications. The result showed less number of stingless bees visited both Chiang Rai and Hungary varieties than that of the European honey bee. The similar numbers of the two pollinators to visit the hybrid cultivar were found. The better pollination parameters were found from the pollination by European honey bee. In addition, the total seed number, good seed weight and good seed number were statistically different from the other treatments. The results from both experiments confirmed the limitations of the selected pollinators. The visiting time, size and the body anatomy of the bees, the floral structure, the readiness for pollination, were all factors affecting seed production of confectionery sunflower.